Antioxidant Activity and Total Phenol Extract of Kecombrang Flower, Stem and Leaves with Different Types of Solutions - Siti Nuryanti; Nurul Latifasari; Rifda Naufalin; Rumpoko Wicaksono; Erminawati Erminawati (Universitas Jenderal Soedirman, 2021)
Kecombrang (Etlingera elatior) is one of the spices which is quite widespread in Indonesia and has many uses. Kecombrang extract has the potential as an antioxidant and natural antimicrobial to extend the shelf life of food products. Extraction was carried out by multilevel maceration method with different types of solvents. This study aims to determine the effect of extraction on the bioactive components of flowers, stems and leaves of kecombrang in different types of solvents and determine the antioxidant activity and total phenols of each type of kecombrang plant extract.The results showed that extraction with distilled water produced the highest total phenol, antioxidant activity and yield on kecombrang leaves. The total phenol extracts of n-hexane leaves, leaves of ethyl acetate, and leaves of kecombrang distilled water were 19.116, 10.276, and 45.008 (mg TAE g db -1) respectively. The antioxidant activity value of flowers, stems and leaves of distilled water solvent kecombrang are 69.754, 72.648, and 78.003 (%) respectively. The yield for flowers, stems and leaves with distilled water solvent is 15.9; 16.6 and 32.95 (%) respectively.